Chatbot engine and Algorithm for Patent Avoidance Design - Hyun Seo, Sung; Hyun Ro, Kwang; Lee, Hoojin (International Journal of Engineering and Technology, 2018)
This paper describes a Chatbot engineand its algorithm that propose a patent avoidance plan as well as the corresponding implementation. In general, when a small company or an individual applicant intends to apply for and apply for intellectual property rights related applications and / or intellectual property rights related matters in order to secure intellectual property rights, a small company or an individual applicant may use intellectual property rights (patent, Trademark, design, copyright) in the field of development and research.In addition, small companies and individual applicants are experiencing a lot of difficulties in securing intellectual property rights and acquiring knowledge on them, because they are specialized work areas that require a lot of legal factors.In addition, a small company or an individual applicant hastily launched new products with the idea that they should quickly market new ideas and new products that could help them to run a business, while ignoring the intellectual property rights. There is a continuing problem of legal problems that canâ€™t be promoted by the monopoly rights of a company that prevails intellectual property rights with products similar to new products.Therefore, this research paper solves the above-mentioned problem by designing the Chatbot engine and implementing the algorithm according to it, and at the same time, it can solve the problems mentioned above, It is one of the researches that have been made to prevent qualitative and material damage without any measures due to the influence of intellectual property rights already prevailed by the invention.In this paper, we propose a Chatbot engine and an implementation algorithm for presenting an avoidance plan related to intellectual property rights before undertaking all tasks for new products.Â